Dionysian Fury and Vibrating Voice: The Physical Performer in Hugo Ball’s Performances and Writings - Syrén Essi (Brill, 2022)
This article concerns Hugo Ball’s artistic practice in performing arts, extending from his prewar years in Expressionist theater to his performances at the Cabaret Voltaire in 1916–1917. In it, I examine how discourses on the crisis of modernity emerge in Ball’s theatrical practice, focusing on the performer’s physical presence in Ball’s performances and theoretical writings. To scrutinize these themes in a wider context of political and cultural discourses on modernity, I discuss the notions conceptualized by Ball and other avant-gardists concerning time and history, illustrating Ball’s view on modernity and German society while providing insight into his performative practice.